1996
DOI: 10.1029/95jd02118
|View full text |Cite
|
Sign up to set email alerts
|

Formation and transport of 2‐nitrofluoranthene and 2‐nitropyrene of photochemical origin in the troposphere

Abstract: The occurrence of 2‐nitrofluoranthene and 2‐nitropyrene in particulate matter collected in urban, suburban, forest, and remote areas located in Europe, America, Asia, and Antarctica was investigated. The results obtained confirm the photochemical origin of these components by gas phase reactions with OH radicals and their ubiquitous occurrence in the troposphere. An important role in their formation and dispersion seems to be played by carbon particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
0
13

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(137 citation statements)
references
References 33 publications
7
117
0
13
Order By: Relevance
“…The results obtained for 1-NPYR levels were similar to those reported in the literature for other cities of the world, like Marseilles [40], Paris [11], Ho Chi Minh [41], Copenhagen [15], Milan [42], Tokyo [43]; among others. It has been observed that 1-NPYR tends to predominate in diesel exhausts and this compound has also been identified in used oils from light-duty diesel engines.…”
supporting
confidence: 76%
“…The results obtained for 1-NPYR levels were similar to those reported in the literature for other cities of the world, like Marseilles [40], Paris [11], Ho Chi Minh [41], Copenhagen [15], Milan [42], Tokyo [43]; among others. It has been observed that 1-NPYR tends to predominate in diesel exhausts and this compound has also been identified in used oils from light-duty diesel engines.…”
supporting
confidence: 76%
“…[3][4][5] NPAHs, which generally exhibit higher mutagenicity and carcinogenicity than the parent PAHs, are also generated from atmospheric reactions of PAHs released into the gas-phase with radical species such as OH and NO 3 radicals and nitrogen oxides. [6][7][8][9][10] OPAHs and OHPAHs, which may show biological effects different from mutagenicity and carcinogenicity, are also known to be secondarily formed via oxidation of PAHs and NPAHs in the atmosphere. 11,12) These derivatized PAHs generally have lower volatility than the par- * To whom correspondence should be addressed: Institute of Medical, Pharmaceutical and Health Sciences, Kanazawa University, Kakuma-machi, Kanazawa, Ishikawa 920-1192, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Depuis peu on utilise l'extraction à l'aide de fluide supercritique [9], mais cette technique prometteuse n'a pas encore été calibrée avec les méthodes classiques. En général il n'est pas nécessaire d'effectuer une purification de l'échantillon, mais un fractionnement entre phase polaire et phase non polaire s'avère cependant souvent recommandable [10]. Certaines analyses demandent une pré-paration supplémentaire.…”
Section: Extraction De La Matière Organiqueunclassified